The Tragedy of Culture and the Objectification of Human Relation: A Reflection on Georg Simmel’s Thoughts - Kurniawan, Kevin Nobel (UI Scholars Hub, 2024)
This article attempts to describe Simmel’s intellectual thoughts, particularly those related to the mode of human relationship. By applying a systematic literature review, this article demonstrates the uniqueness of Simmelian thought in comparison to other major classical sociological thinkers, like Emile Durkheim, Karl Marx, and Max Weber. For Simmel, a macro-level analysis on societal culture can be carried out by focusing on the micro dimension of the everyday life. In this context, Simmel speaks of the tragedy of culture that transpires through the process of objectification, where relationships become increasingly impersonal. At the end, this article provides a commentary on Simmel’s ethical thought and its link to the tragedy of culture.